Pattern recognition and information processing : 13th International Conference, PRIP 2016, Minsk, Belarus, October 3-5, 2016, Revised selected papers /: 13th International Conference, PRIP 2016, Minsk, Belarus, October 3-5, 2016, Revised selected papers. (2017) - Unknown
No abstract available